Volume 1: Turbomachinery 1998
DOI: 10.1115/98-gt-002
|View full text |Cite
|
Sign up to set email alerts
|

Off-Design Performance of a Single Stage Transonic Turbine

Abstract: This paper presents results of rig testing of a transonic, single stage turbine at off-design conditions. Mapping of the 3.4 pressure ratio, 1.9 stage loading turbine ranged from 70% through 120% of design speed and 75% to 125% of design pressure ratio. Results show expansion efficiency dropping over 4% from 100% to 80% of design speed at design pressure ratio, while remaining within half a percent from 90% to 110% of design pressure ratio at design speed. Efficiency lapse rate from equivalent sea-level to cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Vlasic et al [8] (High Work Research Turbine) investigated a single-stage turbine with a pressure ratio of 5 and stage loading of 2.2, the efficiency is reduced by 2.1 per cent when the turbine-cooling rate goes from 0 to 11 per cent. Woinowsky-Krieger et al [9] showed that a 10 per cent reduction in the rotational speed resulted in a decrease of 3 per cent in the efficiency for a single-stage transonic turbine. Recently, the performance testing of a cooled transonic high-pressure turbine with a loading factor of 1.9 was conducted by Neumayer et al [10].…”
Section: Introductionmentioning
confidence: 98%
“…Vlasic et al [8] (High Work Research Turbine) investigated a single-stage turbine with a pressure ratio of 5 and stage loading of 2.2, the efficiency is reduced by 2.1 per cent when the turbine-cooling rate goes from 0 to 11 per cent. Woinowsky-Krieger et al [9] showed that a 10 per cent reduction in the rotational speed resulted in a decrease of 3 per cent in the efficiency for a single-stage transonic turbine. Recently, the performance testing of a cooled transonic high-pressure turbine with a loading factor of 1.9 was conducted by Neumayer et al [10].…”
Section: Introductionmentioning
confidence: 98%
“…In a paper of He,21 it was also mentioned that the non-twist rotor blades lead to a negative incidence near the tip and a positive incidence near the hub. Woinowsky-Krieger et al 5 reported that a transonic turbine had an 8% increase in the blade incidence as the turbine rotational speed changed from 100% to 80%. This is considered to be qualitatively in accordance with the results presented in Figure 10(a).…”
Section: Stator Flow Fields At Different Operating Conditionsmentioning
confidence: 98%
“…In a paper of Woinowsky-Krieger et al, 5 a transonic axial turbine was studied both experimentally and numerically. They found out that the turbine efficiency was only mildly affected by the pressure ratio.…”
Section: Introductionmentioning
confidence: 99%